The Story of Ethiopian Governance: From a centralized public service monopoly to ‘big man’ politics - Gebrehiwot Berhe, Mulugeta (University of Edinburgh, 2025)
This report discusses how the EPRDF, from operating on the logic of a centralized political market, degenerated into an oligopolistic monopoly and later into a neo-patrimonial state that operates on patronage and sustaining disorder while maintaining a simulacrum of an institutionalized state. The report is divided into four parts. The first part discusses the genesis of the EPRDF and its highly centralized public service monopoly in government. The second part discusses the beginning of the end of the EPRDF’s centralized public service monopoly. The third part discusses the complete transformation of the state into what is called a typical African ‘big man’ politics. The fourth and final part is the conclusion.
Keywords: Ethiopia